Evaluation of the immune effect of foot-and-mouth disease virus-like particles derived from Pichia Pastoris on mice and pigs - Li, Zhiyao; Bai, Manyuan; Yin, Shuanghui; Yang, Yan; Dong, Hu; Teng, Zhidong; Sun, Shiqi; Bao, Endong; Guo, Huichen (Frontiers in Microbiology, 2025)
Foot-and-mouth disease (FMD) is an acute, highly contagious, infectious disease that affects cloven-hoofed animals and the healthy development of animal husbandry. Despite the pivotal role of the inactivated FMD vaccine in preventing and controlling the disease, the production and preparation of the inactivated vaccine still present certain safety concerns. Virus-like particles (VLPs), which have a shell structure similar to that of the viruses but lack the genetic material of viruses, have emerged as a prominent area of research on developing next-generation FMD vaccines. In this study, co-expression of P1 and 3C was implemented to obtain the capsid protein of FMD virus (FMDV), and VLPs of FMD were prepared using Pichia Pastoris. Given that the enzymatic activity of 3C is not ideal in acidic yeast cells, the HLH pattern structure was added to the N-terminal end of 3C, which can be anchored near the exit of the nascent peptide chain of ribosomes. Furthermore, the alcohol oxidase (AOX) promoter, which regulates the expression of 3C, was enhanced by mutation. Then, FMDV VLPs were successfully produced in yeast. Immunization of mice and pigs with VLPs resulted in high levels of specific and neutralizing antibodies and provided protection against FMDV in pigs. In conclusion, FMDV VLPs can be successfully produced in P. Pastoris. This offers a new way to develop FMDV VLP vaccines.